Subjectively chosen standards of a hyper feature (Eurasian Journal of Learning and Academic Teaching, 2022)
Subjectively chosen standards of a hyperfeature in a literary text can be expressed by precedent proper names. Sometimes gradual hyperbole is reinforced by lexical or semantic repetition: Each hero is Samson: the strong perishes from the intrigues of the weak and numerous - if his patience bursts, he will crush them and be: crushed himself; or is he just a Gulliver among the Lilliputians, of whom there are so many that in the end they will still take vepx over him (A. Schopenhauer).